HUBUNGAN IKLIM KOMUNIKASI ORGANISASI DENGAN KINERJA PEGAWAI DI REKTORAT UNIVERSITAS RIAU PEKANBARU - Rabit Zanurman; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In any company or government agency, communication experiences thatoccur slowly will form a pattern of organizational communication. This happens alsoin the office of the University of Riau Pekanbaru. Organizational communicationatmosphere has such an important role in influencing the way of life of its members,to whom they spoke, what they like, how they feel, how the activity works, how itgoes, what it wants to achieve and how to adjust to the organization. The purpose ofthis study is to describe how the relationship between organizational communicationClimate with the performance of employees in the office of the rector in University ofRiau Pekanbaru.This research is a quantitative approach of explanation. This study uses asampling technique based on the consideration of Quota Sampling anyone can besampled according to the desired requirements or until the desired quota of the totalpopulation, then gained 64 respondents. Respondents were Employees in the office ofthe Rector in University of Riau who work more than one year, both honorary andCivil Servants.The results of this study indicate that the alternative hypothesis is accepted,which means there is a low correlation between organizational communicationatmosphere with the performance of employees in the office of Rector in University ofRiau. This result is evidenced by the Pearson Correlation value Y = 1.000 + 0.394 Xwith a significant level of α 0.05. The coefficient of determination (r 2) of 0.155 whichmeans that 15.5% of the relationship between organizational communication climatewith the performance of employees in the office of Rector in University of Riau. Whilethe remaining 84.5% is influenced by other variables outside of this study.Key Words : Communication; Organization Communication Climate; EmployeePerformances